Walter Rodney: socialismo afro-caribenho, historiografia e marxismo (1960-1980) - Cavlak, Iuri (Universidade Estadual Paulista (Unesp), 2024)
Trata-se de um estudo sobre Walter Rodney, historiador nascido na Guiana Inglesa em 1942. Rodney se formou em História na West Indie University (Jamaica), sendo um dos pioneiros em abordar a História da África de um ponto de vista marxista. Militou na construção do Socialismo na Tanzania, deixando um enorme acervo de escritos inéditos, os quais me dediquei a pesquisar e analisar. Morreu assassinado na Guiana em 1980.

This is a study of Walter Rodney, a historian born in British Guiana in 1942. Rodney graduated in History from West Indie University (Jamaica) and was one of the pioneers in approaching African History from a Marxist perspective. He was a militant in the construction of Socialism in Tanzania, leaving behind a huge collection of unpublished writings, which I dedicated myself to researching and analyzing. He was assassinated in Guyana in 1980.
Walter Rodney: Afro-Caribbean socialism, historiography and marxism
Keywords: História da África; Historiografia; Marxismo